Persuasive Communication in an Educational Perspective - Akbar Syamsuddin; Samsinar S (State Islamic Institute of Bone, Indonesia, 2021)
This study discusses the concept of persuasive communication from an educational perspective, the importance of persuasive communication in education, the obstacles experienced by teachers in applying persuasive communication and persuasive communication models in education. This research is library research with descriptive-qualitative approach. The method and analysis used is inductive qualitative analysis. Inductive qualitative data analysis is an analysis based on the data obtained, then developed into answers to the problems in this study, and searched for data repeatedly so that the data collected can be known to be accepted or rejected. The results of the study indicate that persuasive communication in education is a communication interaction that occurs between teachers and students in an educative and humanistic manner with the aim of changing the attitudes, behavior and views of students so that learning activities run well and achieve the learning objectives that have been set. There are several teacher barriers in persuasive communication, namely biological, psychological, and gender barriers, both from the teachers themselves and from students. Furthermore, persuasive communication is very important for students because it will improve students' cognitive and social abilities, generate learning motivation and students' self-confidence and provide benefits, maintain and improve positive relationships and attitudes between teachers and students. Teachers can apply this persuasive communication by adjusting to learning situations and conditions through various models, both equation models, separate balanced, unbalanced separately, monopoly, linear, interactive and transactional.